Role of Overcooling in Preserving Clonogenic Properties of Fibroblast-Like Progenitor Cells of Human Fetal Liver After Cryopreservation - Skorobogatova, N. G.; Grischuk, V. P.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2006)
Effect of different freezing conditions on human fetal liver (HFL) cell viability and colony-forming activity of HFL fibroblast-like progenitor cells (FPCs) was investigated. This progenitor type was established to be a high sensitive to a damaging effect of overcooling. Overcooling reduction at a slow three-step freezing enables a successful cryopreservation of FPCs in primary suspension of HFL cells with preservation of their clonogenic properties.